Strategi Mempertahankan Kepercayaan dan Reputasi Merek SNSBWORLD Berbasis Komunitas - Suci Afrilia Nabila; Ahmad Taufiq Maulana Ramdan (Komunika : Jurnal Ilmiah Komunikasi, 2025)
This study aims to analyze how SNSBWORLD, a community based streetwear brand originating from Bandung, builds and maintains public trust and brand reputation within the rapidly evolving landscape of urban fashion. SNSBWORLD has grown organically through social closeness between the brand owner, community members, and the public, enabling its communication strategy to rely heavily on interpersonal relationships and community driven activities rather than large scale commercial promotion. Employing a descriptive qualitative approach, this research collected data through in depth interviews, observations of online and offline community activities, and content analysis of Instagram and TikTok posts. The findings indicate that SNSBWORLD’s brand trust is strongly shaped by its consistent visual identity, authenticity of creative values, and transparent communication, particularly in addressing criticism and public feedback. Organic testimonials from community members and collective experiences during offline events such as gatherings, fun sport activities, and creative collaborations play a significant role in strengthening emotional ties between the brand and its audience. These findings align with the Relationship Management Theory, which highlights the importance of two way communication, long term commitment, and emotional engagement in building sustainable organization public relationships. The study concludes that SNSBWORLD’s community centered approach is effective in fostering public loyalty and enhancing brand reputation, as it is grounded in authenticity, direct interaction, and a naturally developed sense of belonging. This research contributes to the field of digital Public Relations by demonstrating that brand reputation can be sustainably developed through authentic and participatory social relationships, particularly for local brands rooted in community culture. Keyword : brand, reputation, community, trust, SNSBWORLD.